Pengembangan Lanjut Aplikasi GETAS (Geotagging Brantas) untuk Geotagging Sungai Brantas - Irsyad Rifqi Arrazaq; Herman Tolle; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Currently, the condition of cleanliness in the river needs to be considered. Due to the lack of public awareness of the cleanliness of the river, the current cleanliness of the river is not maintained. One of the impacts caused by the lack of public awareness of the cleanliness of the river is that there is already a lot of garbage in the river. This of course will affect the people who live in the area around the river because it can cause flooding when it rains heavily or it can make them uncomfortable because of the pungent smell of garbage thrown carelessly in the river. The research with the title "Further Development of GETAS Applications (Geotagging Brantas) for Geotagging the Brantas River" will produce outputs that aim to share information about the state of the river and raise awareness of people living in the area around the river to be more concerned about the cleanliness of the river ecosystem. GETAS will use Global Positioning System sensors and cameras to map rivers.